Effects of exogenous abscisic acid on the growth and cadmium accumulation of lettuce under cadmium-stress conditions. Issue 6 (2nd May 2020) - Tang, Yi; Wang, Liming; Xie, Yongdong; Yu, Xuena; Li, Huanxiu; Lin, Lijin; Liao, Ming'An; Wang, Zhihui; Sun, Guochao; Wang, Xun; Liang, Dong; Xia, Hui; et al.
ABSTRACT: Abscisic acid (ABA) is an important hormone that can regulate the heavy-metal uptake of plants. In this study, exogenous ABA was applied to lettuce ( Lactuca sativa ) grown under cadmium (Cd)-stress conditions, and the effects of exogenous ABA on the growth and Cd accumulation of lettuce were evaluated. The results showed that treatment of Cd significantly decreased biomass and increased Cd content of lettuce compared with the control. The shoot biomass increased after spraying 1, 5 and 10 μmol/L ABA, and the root biomass increased after spraying 1–20 μmol/L ABA compared with the treatment of Cd. The Cd content in shoots significantly decreased when exposed to different ABA concentrations. The lowest Cd content in shoots of lettuce was produced by the ABA concentration of 5 μmol/L, with decreased by 23.60% compared with the treatment of Cd. Therefore, spraying ABA effectively alleviated Cd toxicity and reduced Cd uptake in the edible parts of lettuce, and 5 μmol/L ABA was the optimal dose.